D2 dopamine receptor up-regulation, treatment response, neurological soft signs, and extrapyramidal side effects in schizophrenia: a follow-up study with 123I-Iodobenzamide single photon emission computed tomography in the drug-naive state and after neuroleptic treatment - Schröder, Johannes; Fauth Silvestri, Simone; Bubeck, Bernd; Karr, Markus; Demisch, Sibylle; Scherrer, Sabine; Geider, Franz Josef; Sauer, Heinrich (Biological psychiatry, 1998)
Background: Animal and postmortem studies indicate that neuroleptic therapy may induce D2 dopamine receptor up-regulation in the basal ganglia. Methods: To address this phenomenon in a clinical study, we investigated the D2 dopamine receptor binding in 15 DSM-III-R schizophrenics in the drug-naive state and 3 days after completion of a standardized neuroleptic therapy (benperidol 12-16 mg/day, for 25 days) using single photon emission computed tomography (SPECT). SPECT scans were obtained 2 hours after intravenous injection of 185 MBq 123I-iodobenzamide. For analysis, basal ganglia to frontal cortex (BG/FC) ratios were calculated and the patient sample was subgrouped into patients with a favorable versus a poor treatment response. Results: Neuroleptic treatment led to decreased BG/FC ratios in patients with a favorable response, but increased ratios in the poor responders (df = 1, F = 4.1, p = .06). Changes of BG/FC ratios were significantly correlated with extrapyramidal side effects but not with neurological soft signs. Conclusions: Our findings suggest that neuroleptic therapy may induce D2 dopamine receptor up-regulation in a subgroup of patients characterized by poor treatment response and pronounced extrapyramidal side effects.
Gesehen am 26.01.2021